Effects of Muck Size Distribution on Scooping Operations - S. P. Singh; Turgut Yalcin (International Society of Explosives Engineers, 2002)
The physical characteristics of blasted rock are fundamental variables affecting the economics of mining operations and are in fact the basis for evaluating the quality of a blast. A study was designed with the objective of quantifying the effect of muck size distribution on scooping operations in a mine.